Farmers’ Readiness for Organic Farming: A Study of Aligarh District in Uttar Pradesh (Indian Journal of Extension Education, 2022)
The study was conducted in the purposively selected Aligarh district of Uttar Pradesh to assess the readiness of farmers for organic farming. The readiness of the farmers for organic farming was perceived in terms of conducive agricultural profile, a favorable attitude, sufficient knowledge and availability of required manpower and inputs for organic farming. The sample size of the study was 240 farmers spreading in twelve villages over six blocks of the district. Animal husbandry with agriculture, growing of pulses, millets, sesbania (for green manuring) and having neem trees (Azadirachta indica) were found already existing farm practices building supporting ground for the organic farming. Overall farmers were having favourable attitude towards organic farming. But, attitude towards the implementation aspect of organic farming was not as strong as towards impact on the environment and soil health, and economic benefits of organic farming. Farmers knew cultural practices related aspects of organic farming but lacking in knowledge regarding trap crops and bio-agents. There is a need to provide institutional support in creating awareness in technological advancement of organic farming, diversification of cereal based cropping system with the inclusion of leguminous crops and in increasing accessibility of off-farm organic inputs.